Factors related to non-mammographic visualization in locally advanced breast carcinoma - Watanabe, Anapaula Hidemi Uema; Saito, Marcio Mitsugui Saito; Cabral, Bruno Eduardo Fernandes; Vieira, René Aloisio da Costa (Mastology, 2020)
Objective: To determine the rate and factors related to non-visualization of locally advanced breast cancer (LABC) by mammography. Method: Prospective, cross-sectional study, conducted in a cohort of consecutive patients with LABC treated at a tertiary cancer hospital. All patients were systematically examined and underwent high-resolution mammography (conventional equipment) in two views (craniocaudal and mediolateral oblique). A blind study was performed in which mammograms were mixed with routine and where radiologists were unaware of the clinical data. Three radiologists evaluated the examinations. In the patients in whom the findings were negative, the possible causes responsible for not identifying the tumor on mammography were evaluated. After the radiological report, the examinations were reviewed, and the radiological data were added to the standard form, making up the database of the present study. Descriptive statistics were used to compare factors related to non-visualization of tumors, namely the chi-square test and the Mann-Whitney test. Result: Eighty-five patients were evaluated. The average size of the tumors was 6.96 cm, and 20% of cases were not identified on mammography. Among the causes, 76.4% had dense parenchyma, 17.6% were not visible on examination, and in 5.8%, the lesion was not noticed by the radiologist (false negative examination). The only factor found when LABC was not identified was the type of breast parenchyma (p=0.04).Conclusion: Clinical history and changes in physical examination should be considered in the report to the radiologist. High breast density was the major obstacle to mammography diagnosis.